2004
DOI: 10.1113/jphysiol.2004.069088
|View full text |Cite
|
Sign up to set email alerts
|

Excitability changes in human forearm corticospinal projections and spinal reflex pathways during rhythmic voluntary movement of the opposite limb

Abstract: Rhythmic movements brought about by the contraction of muscles on one side of the body give rise to phase-locked changes in the excitability of the homologous motor pathways of the opposite limb. Such crossed facilitation should favour patterns of bimanual coordination in which homologous muscles are engaged simultaneously, and disrupt those in which the muscles are activated in an alternating fashion. In order to examine these issues, we obtained responses to transcranial magnetic stimulation (TMS), to stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 44 publications
6
91
0
1
Order By: Relevance
“…MEP amplitude was determined as the peak-to-peak amplitude following TMS. Trials in which root mean squared (RMS) EMG exceeded 10 ”V (Carson et al 2004) during the 40 ms immediately preceding the TMS pulse were discarded.…”
Section: Transcranial Magnetic Stimulation (Tms) and Electromyographymentioning
confidence: 99%
“…MEP amplitude was determined as the peak-to-peak amplitude following TMS. Trials in which root mean squared (RMS) EMG exceeded 10 ”V (Carson et al 2004) during the 40 ms immediately preceding the TMS pulse were discarded.…”
Section: Transcranial Magnetic Stimulation (Tms) and Electromyographymentioning
confidence: 99%
“…It has been recently shown that in sitting volunteers performing voluntary foot (Baldissera et al, 2002) or contralateral wrist (Carson et al, 2004) flexions/ extensions, the excitability of corticospinal pathways targeting the resting wrist muscles is modulated in phase with movements, whereas the H-reflex and f-waves are depressed markedly during contraction of homologous muscles of the contralateral forearm (HortobĂĄgyi et al, 2003;Carson et al, 2004). Moreover, in standing subjects, overt electromyographic activity in forearm muscles has been described to accompany movements of the contralateral forearm (Slijper and Latash, 2000) or ipsilateral foot (Baldissera and Esposti, 2005).…”
Section: Side Differences In Motor-related Fmri Spinal Signalsmentioning
confidence: 99%
“…Larger MEPs reflect greater CST excitability. MEPs were discarded if the root-mean square (RMS) of the EMG exceeded 15 V (Carson et al, 2004) during the 70 msec immediately preceding the TMS pulse. No more than three trials were discarded per image condition per participant.…”
Section: Data Reduction and Statistical Analysesmentioning
confidence: 99%